A game of secrets - Day, Zuri (Harlequin desire, 2023)
Jake Eddington isn't the type to be tied down -- until he meets her at a masquerade party. But then, the best night of his life becomes the worst when their masks come off. His temptress is none other than Sasha McDowell -- his best friend's sister. The woman Jake's supposed to protect! Away from her controlling family, Sasha's determined to explore her wild side. But that spectacular night with Jake is unexpectedly complicated, for his business and her reputation. Yet their connection can't be ignored -- even if their tryst ignites a scandal.